2012
DOI: 10.1086/666343
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Randomized Trial to Evaluate the Effect of a Multimodal Hand Hygiene Improvement Strategy in Primary Care

Abstract: This study has demonstrated that hand hygiene compliance in primary healthcare workers can be improved with a multimodal hand hygiene improvement strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(62 citation statements)
references
References 38 publications
2
57
1
2
Order By: Relevance
“…[2][3][4]12 The World Health Organization (WHO) has recommended a multimodal strategy to improve and sustain hand hygiene compliance, 13 and its effectiveness has been demonstrated. [14][15][16][17][18] The Institute for Healthcare Improvement (IHI) has supported health systems in their own initiatives. In doing so, it has developed tools and methods.…”
mentioning
confidence: 99%
“…[2][3][4]12 The World Health Organization (WHO) has recommended a multimodal strategy to improve and sustain hand hygiene compliance, 13 and its effectiveness has been demonstrated. [14][15][16][17][18] The Institute for Healthcare Improvement (IHI) has supported health systems in their own initiatives. In doing so, it has developed tools and methods.…”
mentioning
confidence: 99%
“…However, in view of the available national and international literature on HH, low compliance with established practices is evident, jeopardizing both user and professional safety (8,11) . In the extra-hospital environment, these data are still incipient (13)(14)(15)(16)(17)(18) . A Spanish study, carried out at PHC and in a hospital environment, found gaps in the knowledge of health professionals regarding the concept of hands hygiene and the use of alcohol solution (16) .…”
Section: Discussionmentioning
confidence: 99%
“…A study carried out at the PHC in Madrid, where adherence to HH was observed at the five points indicated by the World Health Organization (WHO), resulted in a value of 8.1% of adherence (13) . In Nigeria, a study showed that nurses demonstrated good knowledge regarding infection control, but did not reflect on the level of adherence to practices (26) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is a simple, inexpensive, and effective measure, hand hygiene compliance often remains obstinately low, with estimated compliance rates below 50%. 31,32 The ideal targets for hand hygiene compliance rates have been estimated in a number of studies. McBryde et al 11 estimated that a compliance rate of at least 48% was required to eradicate MRSA colonization, whereas the figure estimated by Pressley et al 22 was 70% for the same pathogen.…”
Section: Effectiveness Of Infection Control Measures Investigated Usimentioning
confidence: 99%